Some relationships between body weight and body measurements of goats - Githae, J.; Kitivo, D.; Mwaniki, H.; Ogutu, E.; Rakoczi, G. (1975)
Five body measurements were compared to body weights in goats of different ages and in various locations. Formulae included for calculating average body weight from body measurements.